Determinants of Rubber Exports on Economic Growth in North Sumatra Province - Pinem, Syukri Aiman; Ridwan, Muhammad; Batubara, Maryam (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the determinants of rubber exports to economic growth in North Sumatra province for the period 2013 to 2023. The variables of rubber determinants used in this study are the price of rubber, the amount of rubber production, and the rupiah exchange rate. The data used is secondary data by collecting annual reports interpolated into quarters published by Bank Indonesia, Central Bureau of Statistics. Data analysis techniques using classical assumption tests and continued with multiple linear regression analysis using SPSS 2022. The results of this research are the determinants of rubber exports with variable prices have a negative and significant effect on economic growth, variable production quantities have a positive and significant effect on economic growth and variable exchange rates have a negative effect on economic growth. Simultaneously determinant of rubber exports affect economic growth with a contribution of 41.8 percent.